2008
DOI: 10.1164/rccm.200710-1513oc
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Is Effective against Experimental Malignant Pleural Effusion

Abstract: ZA is effective against experimental MPE, suggesting that this intervention should be considered for testing in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
21

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 47 publications
3
62
1
21
Order By: Relevance
“…Mice received 1 mg/kg intraperitoneal TRFK5, which provides prolonged bioactivity (37), in ''prevention'' (Days 0 and 8) and ''regression'' (Day 8) protocols, the latter aimed at therapy of established MPEs developing around Day 8 (13,38).…”
Section: Il-5 Neutralizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice received 1 mg/kg intraperitoneal TRFK5, which provides prolonged bioactivity (37), in ''prevention'' (Days 0 and 8) and ''regression'' (Day 8) protocols, the latter aimed at therapy of established MPEs developing around Day 8 (13,38).…”
Section: Il-5 Neutralizationmentioning
confidence: 99%
“…Tissue sections were immunolabeled as described previously (13)(14)(15)38), or stained with Biebrich scarlet for eosinophils (39).…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…The results of previous studies have shown that ZOL has anticancer activity against several human neoplasms such as leukemia, breast, prostate, and pancreatic cancers in vivo . 21, 22, 23, 24 The mechanism underlying these anti‐proliferative effects is thought to involve the inhibition of RAS GTPase prenylation 25, 26…”
mentioning
confidence: 99%